Pengaruh Pelatihan Kerja Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Kencana Abadi Jaya - Syarief Eko Margono; Taat Kuspriyono (Jurnal Manajemen Riset Inovasi, 2024)
In an ever-changing and developing business world, PT. Kencana Abadi Jaya faces constant pressure to remain competitive and grow. Optimal employee performance is a key factor in the success of the company, influenced by job training and work motivation. This study aims to: Determine the influence of job training on employee performance, determine the influence of work motivation on employee performance, and determine the simultaneous influence of job training and work motivation on employee performance at PT. Kencana Abadi Jaya. The research method used is quantitative, with data collected through surveys, interviews, observations, literature studies, and documentation during the period of April - June 2024. The population in this study is 150 employees, with a sample of 110 employees taken based on the Slovin method. Data were analyzed using SPSS with data quality tests, classical assumption tests, multiple linear regression, t-test, F-test, and the coefficient of determination. The results show that: Partially, job training has a positive and significant effect on employee performance, partially, work motivation has a significant effect on employee performance, and simultaneously, job training and work motivation have a positive and significant effect on employee performance at PT. Kencana Abadi Jaya.